(untitled) (Semiárida, 2020)
With the aim of evaluate the impact in vegetation and soil of a water redistribution work in steppe area, a test developed during 2010 and 2011 in the ecological area of Sierras y Mesetas Occidentales of Chubut NW. Forage species were sowed and the impact of the spring-winter irrigation was evaluated on the sowing, on the natural vegetation and on soil characteristics. The sowing failed in spite of the contributions extras of water, the presence of dampness in the soil did not manage to coincide with sufficient thermal accumulation. The natural vegetation showed positive changes under irrigation. The analyzed soil variables were modified in the last measurement revealing an increase in the values of salinity though very far from reaching problematic levels.